Fractional-Order Modeling and Analysis of Nanoparticle Transport in Magnetohydrodynamic Blood Flow Through a Stenosed Artery - Isah Abdullahi; Ali Musa (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
This study presents an extended fractional-order mathematical model for blood flow through a stenosed artery under the combined effects of a magnetic field, porous medium, chemical reaction, and nanoparticle diffusion. The study aims to provide a more accurate and physiologically relevant representation of nanoparticle transport in pathological arterial flow conditions. The governing nonlinear equations for momentum and mass transfer were formulated and solved using a semi-analytical approach involving modified Bessel and Mittag–Leffler functions. Model validation through comparison with existing results showed excellent agreement, confirming the reliability of the proposed formulation. The parametric analysis revealed that increasing the chemical reaction parameter and Schmidt number reduced nanoparticle concentration, whereas a higher fractional order enhanced mass transport by weakening memory effects. The study concludes that the fractional-order framework offers an improved description of nanoparticle transport in stenosed arterial blood flow and contributes to the advancement of mathematical modeling for physiologically realistic hemodynamic analysis.